Pengaruh Keadilan Prosedural Terhadap Kepuasan Kerja Karyawan Pada CV. Planet Swalayan Marpoyan Kota Pekanbaru - Rahmat, Yogie; Nainggolan, Eris M. (Eko dan Bisnis: Riau Economic and Business Review, 2025)
Research conducted on CV. PLanet Supermarket Marpoyan Pekanbaru City. The purpose of this study is to determine the effect of procedural justice on employee job satisfaction at CV. Planet Supermarket Marpoyan Pekanbaru City with a sample of 91 employees. Based on the research results it is known that there is an effect of procedural justice on employee job satisfaction at CV. Planet Swalayan Marpoyan Pekanbaru City simple linear regression is as follows Y = 23,173 + 0,284 X. This equation means that when Procedural Justice (X) does not exist or is zero, employee satisfaction (Y) is still obtained by 23,173 units. While the effect of Procedural Justice (X) on employee satisfaction (Y) is positive as evidenced by the results of the regression coefficient (b) of 0.284 which means that every increase in Procedural Justice (X) of one unit will increase employee satisfaction (Y) on CV . Planet Supermarket Marpoyan Pekanbaru City of 0.284 units. The results of SPSS data processing show that there is a tcount of 1,996, so the hypothesis test is tcount = 1,996 > ttable = 1,986 and also a significance level of 0.049 <0.05 which means that there is a significant influence between Procedural Justice (X) on employee satisfaction (Y) at CV. Planet Supermarket Marpoyan Pekanbaru City. In the coefficient test, the R Square value is 0.043. This means that the contribution of the Influence of Procedural Justice (X) to Employee Satisfaction (Y) at CV. Planet Supermarket Marpoyan City of Pekanbaru is 4.3%. While the remaining 95.7% is influenced by other variables not described in this study